Family Group Conferences as a Shared Decision-Making Strategy in Adults Mental Health Work - Ramon, Shulamit (Frontiers in Psychiatry, 2021)
Family Group Conferences as a shared decision- making strategy in adults mental health work Family Group conferences (FGM) provide a system by which a client and their family reach jointly key intervention decisions, from a number of options proposed by professionals. The system originated in child protection social work. Conceptually FGC is based on the assumption that the family is a social system which can be a supportive framework for an individual with a variety of difficulties, including mental ill health. Reaching a family network agreement can lead to long term positive outcomes in self- confidence and social relationships. This strategy of shared decision making (SDM) can re-unite the family around the client’s needs and wishes. It fits well the strengths based and recovery- oriented approach to mental ill health. Methodologically, this article provides a scoping narrative of the existing research about FGC in the context of adult mental health. Two community case studies consisting of videos of a mother experiencing mental ill health and a daughter are analysed in terms of how they experienced the FGCs they were involved in setting up. The research analysis looks at both the process and the outcomes of FGCs. The key findings demonstrate a high level of satisfaction of participation in the FGC meeting, while the evidence pertaining to the outcomes is inconclusive. There are very few systematic review studies, or comparative studies of different approaches to family decision making, and there are no studies which offer cost effectiveness analysis. Discussion: The observed gap between the satisfaction from the process of FGC by the participants versus the inconclusive outcomes relates to the implementation process , in which the decisions made by the family are tested. The lack of sufficient research evidence, despite the existence of promising research, is an issue that needs to be tackled more systematically, although comprehensive evaluation of FGC is complex. In conclusion, FGC is a promising strategy of SDM in adult mental health. The research evidence indicates the need to exploring further its underlying values, implementation process, evaluative methodology and methods.